Literature Review: The Factors influence of the Performance of Government Organizations - Subroto subroto; Ari Saptono; Mohammad Sofwan Effendi (Jurnal Akuntansi dan Pajak, 2022)
Achievement of Organizational Performance for leaders is the art of leadership and strategy that depends on the capabilities, intuition, creativity and experience in optimizing human resources and available facilities. Although the infrastructure is already available, triggering and strengthening factors are needed through organizational culture in order to achieve effective organizational performance and sustainability. This article tries to explore the factors that influence the accountability of organizational performance. The findings state that strategic leadership, human resource competence and information and technology capabilities through organizational culture moderation will have a positive effect on organizational performance accountability. It is hoped that this article will be useful for the leaders of government organizations in optimizing resources and facilities and budgets in order to perform the best public services to the community with various changes and challenges in the future.